Intragenic CNVs for epigenetic regulatory genes in intellectual disability: Survey identifies pathogenic and benign single exon changes. Issue 11 (17th October 2016) - Zahir, Farah R.; Tucker, Tracy; Mayo, Sonia; Brown, Carolyn J.; Lim, Emilia L.; Taylor, Jonathan; Marra, Marco A.; Hamdan, Fadi F.; Michaud, Jacques L.; Friedman, Jan M.
Abstract : The disruption of genes involved in epigenetic regulation is well known to cause Intellectual Disability (ID). We reported a custom microarray study that interrogated among others, the epigenetic regulatory gene‐class, at single exon resolution. Here we elaborate on identified intragenic CNVs involving epigenetic regulatory genes; specifically discussing those in three genes previously unreported in ID etiology— ARID2, KDM3A, and ARID4B . The changes in ARID2 and KDM3A are likely pathogenic while the ARID4B variant is uncertain. Previously, we found a CNV involving only exon 6 of the JARID2 gene occurred apparently de novo in seven patients. JARID2 is known to cause ID and other neurodevelopmental conditions. However, exon 6 of this gene encodes one of a series of repeated motifs. We therefore, investigated the impact of this variant in two cohorts and present a genotype–phenotype assessment. We find the JARID2 exon 6 CNV is benign, with a high population frequency (>14%), but nevertheless could have a contributory effect. We also present results from an interrogation of the exomes of 2, 044 patients with neurocognitive phenotypes for the incidence of potentially damaging mutation in the epigenetic regulatory gene‐class. This paper provides a survey of the fine‐scale CNV landscape for epigenetic regulatory genes in the context of ID, describing likely pathogenic as well as benign single exon imbalances. © 2016 Wiley Periodicals, Inc.